Agissea teruruhau sp. nov. (Peyssonneliales, Rhodophyta) and epiphyte Piriora waewaeiti gen. & sp. nov. (Gigartinales, Rhodophyta) from Manawatāwhi, New Zealand. Issue 1 (2nd January 2023) - Nelson, Wendy; Ngauma, Bruce; Norman, Jerry H.; Ringham, Sandi; Sutherland, Judy
ABSTRACT: Phylogenetic analyses resolved that specimens from Manawatāwhi/Three Kings Islands in northern New Zealand, formerly identified as Sonderophycus coriaceus, belong to the genus Agissea (Peyssonneliales). This species is dark red, prostrate and robust, with leathery, fan-shaped lobes and is described here as Agissea teruruhau . It was found to serve as a host to a very small red algal epiphyte described here as Piriora waewaiti gen . & sp. nov . While phylogenetic analyses have placed Piriora in the Gigartinales, the familial placement of this genus has been unable to be resolved. Manawatāwhi/Three Kings Islands is a group of small islands known to harbour a rich marine biota with many endemic species, and the description of these taxa has increased the reported endemic algal flora of the islands. In addition, the phylogenetic analyses have confirmed the presence of Olokunia boudouresquei and a further three species of Peyssonneliales in the New Zealand flora, belonging to the genera Olokunia, Peyssonnelia and Seiria .